Synthesis of polymeric microcapsules by interfacial-suspension cationic photopolymerisation of divinyl ether monomer in aqueous suspension. Issue 6 (13th January 2017) - Benedetti, M.; Congdon, T. R.; Bassett, S. P.; Alauhdin, M.; Howdle, S. M.; Haddleton, D. M.; Pisano, R.; Sangermano, M.; Schiller, T. L.
Abstract : Polymeric microcapusles have been synthesised with a markedly more hydrophillic monomer than previously reported, triethylene glycol divinyl ether, using cationic photopolymerisation in an aqueous environment. Abstract : Polymeric microcapusles have been synthesised with a markedly more hydrophillic monomer than previously reported, triethylene glycol divinyl ether, using cationic photopolymerisation in an aqueous environment. Characterisation by NMR and SEM show that the particles are formed with low dispersity with a size of approximately 1 μm in spite of the expected inhibition in aqueous conditions. Furthermore, supercritical carbon dioxide has been used to generate silver nanoparticles which distribute throughout the shell of the microcapsules further illustrating the structure of these capsules with characterisation by TEM and SAXS.